Remobilization of Dry Matter, Nitrogen and Phosphorus in Durum Wheat as Affected by Genotype and Environment - Silvia Pampana; Marco Mariotti; Laura Ercoli; Alessandro Masoni (Italian Journal of Agronomy)
Field studies were carried out to determine dry matter (DM), nitrogen (N) and phosphorus (P) assimilation until anthesis and DM, N and P remobilization during grain filling in wheat. Twentyfive durum wheat (Triticum durum L.) varieties were grown in Tuscany at Grosseto and at Arezzo. At Grosseto 76% of DM was assimilated during pre-anthesis while at Arezzo the amount was 81%. At Grosseto 44% and at Arezzo 35% of N was accumulated until anthesis, while 33% of P was stored until anthesis in both localities. Cultivar differences in DM and N remobilization were positively related to pre-anthesis dry matter and N content at anthesis (r > 0.74). Environmental contraints on carbon, N and P availability in the plant are crucial factors in determining grain yield and N and P content in grain, affecting both accumulation and remobilization. In the low rainfall site of Grosseto, most of the grain yield originated from dry matter accumulation, while in the wetter environment of Arezzo remobilization and accumulation contributed equally to grain yield. Conversely, at Grosseto grain N content relied most on remobilization and at Arezzo remobilization and accumulation contributed equally. Finally, at Grosseto and at Arezzo accumulation of P was the main source of grain P content.